2017
DOI: 10.1016/j.jns.2016.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel and ischemic stroke outcomes by smoking status: Smoker's paradox?

Abstract: Background and purpose Active smokers with myocardial infarction were shown to have enhanced benefit with clopidogrel compared with aspirin. Whether this “paradox” exists in ischemic stroke patients is unknown. We aimed to investigate whether smoking status has a differential impact on the efficacy of clopidogrel vs. aspirin in patients with non-cardioembolic strokes. Methods This single-center study retrospectively assessed 1792 non-cardioembolic ischemic stroke patients discharged from January 2013 to Octo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…There were a total of 3843 ischemic stroke patients in the SRICHS in 2009. We included 2740 patients 63.9 ± 12.5 62.7 2650 Taiwan 0.0 Zhang [ 25 ] 2017 Retrospective cohort study We retrospectively reviewed the prospectively maintained stroke registry of a single medical center (Xuanwu Hospital) comprising 1910 non-cardiogenic ischemic stroke patients consecutively discharged from January 2013 to October 2014 58.68 ± 11.60 95.4 1792 China 1.0 Total 18 studies 987,074 …”
Section: Resultsmentioning
confidence: 99%
“…There were a total of 3843 ischemic stroke patients in the SRICHS in 2009. We included 2740 patients 63.9 ± 12.5 62.7 2650 Taiwan 0.0 Zhang [ 25 ] 2017 Retrospective cohort study We retrospectively reviewed the prospectively maintained stroke registry of a single medical center (Xuanwu Hospital) comprising 1910 non-cardiogenic ischemic stroke patients consecutively discharged from January 2013 to October 2014 58.68 ± 11.60 95.4 1792 China 1.0 Total 18 studies 987,074 …”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Maruyama et al [ 46 ] demonstrated that smokers achieve significantly lower platelet reactivity values (128 vs. 167 PRU, p = 0.002) than nonsmokers and, additionally, the incidence of clopidogrel resistance is significantly lower in smokers (12.9% vs. 25.9%; p = 0.033). Zhang et al [ 47 ] concluded that the antiplatelet effect of clopidogrel in ischemic stroke patients is much better in smokers and showed a statistical trend for a reduced risk of recurrent vascular events with clopidorel than with aspirin [ 47 ]. The explanation of the above dependencies is believed to be the activation of the cytochrome P450 complex by nicotine, which may result in a more efficient metabolization of clopidogrel by the liver, leading to increased platelet inhibition [ 46 ].…”
Section: Factors Influencing Clopidogrel Resistancementioning
confidence: 99%
“…ischemic stroke is one of the most frequently occurring conditions among older populations, accounting for a large proportion of the morbidity and mortality rates worldwide (1,2). Smoking habits, hypertension and diabetes have all been listed as risk factors of ischemic stroke (3,4). ischemic stroke occurs following a blockage in an artery leading to the brain; thus, an insufficient supply of oxygen and glucose reaches the brain that is required for cellular energy, which culminates in irreparable damage (5,6).…”
Section: Introductionmentioning
confidence: 99%